2012
DOI: 10.1161/circresaha.111.261750
|View full text |Cite
|
Sign up to set email alerts
|

Increased Superoxide and Endothelial NO Synthase Uncoupling in Blood Vessels of Bmal1-Knockout Mice

Abstract: Rationale Disruption of the circadian clock in mice produces vascular dysfunction as evidenced by impairments in endothelium-dependent signaling, vasomotion, and blood vessel remodeling. Although the altered function of endothelial NO synthase and the overproduction of reactive oxygen species are central to dysfunction of the endothelium, to date, the impact of the circadian clock on endothelial NO synthase coupling and vascular reactive oxygen species production is not known. Objective The goals of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 65 publications
1
84
0
2
Order By: Relevance
“…An increase in nitric oxide production in tubular cells is an alternative mechanism that could explain this phenomenon. 34,35 Collectively, functional analysis of Bmal1 lox/lox /Ren1 d Cre mice has shown that the local renal circadian clocks are involved in a variety of specific renal functions and BP control. The specificity in establishing genotype-phenotype correlations in circadian clock-deficient models consists in the highly pleiotropic role of circadian clocks on both transcriptional/ translational and functional levels.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in nitric oxide production in tubular cells is an alternative mechanism that could explain this phenomenon. 34,35 Collectively, functional analysis of Bmal1 lox/lox /Ren1 d Cre mice has shown that the local renal circadian clocks are involved in a variety of specific renal functions and BP control. The specificity in establishing genotype-phenotype correlations in circadian clock-deficient models consists in the highly pleiotropic role of circadian clocks on both transcriptional/ translational and functional levels.…”
Section: Discussionmentioning
confidence: 99%
“…These frozen tissues were sectioned at a thickness of 8 μm and incubated with dihydroethidium (DHE; 5 μM; Life Technologies) for 30 min at 37°C. 2 Some sections were pretreated with superoxide dismutase-polyethylene glycol (PEG-SOD; 300 U/ml)/catalase-polyethylene glycol (PEG-CAT; 200 U/ml) or Apocynin (250 μM) or L-NG-Nitroarginine Methyl Ester (L-NAME; 1 mM) before incubation with DHE for 10 min at 37°C. The aortic specimen were visualized by Olympus IX81 confocal fluorescence microscopy using an excitation at 546 ± 25 nm band-pass filter, emission at 590 nm long-pass filter followed by a 640 ± 25 nm band-pass filter.…”
Section: Measurement Of Superoxide In In Vitro Cell Cultures Andmentioning
confidence: 99%
“…1 Uncoupling of eNOS has been shown to be central to robust superoxide generation and the associated vascular dysfunction. 2 Increased levels of asymmetric NG, NG-dimethyl arginine (ADMA-a substrate analog of L-arginine) in circulation have also been shown in diabetic patients limiting the availability of L-arginine to eNOS. 3 In vitro studies from our laboratory and reports from other investigators have shown that the regulation of eNOS activity is mediated by heat shock protein-90 (Hsp-90).…”
mentioning
confidence: 99%
“…As such, Period2 is important for healthy functions and recruitment of endothelial progenitor cells to growing vessels in mice; animals in which the period2 gene has been mutated and rendered dysfunctional exhibit vascular senescence and a lack of ischemia-induced angiogenesis in the hind-limb muscle tissue [37]. In addition to the direct regulation of tumor cell dedifferentiation by the pathological tumor cell circadian clock [3], clock disruption also lead to elevated intracellular ROS [38], which in turn could drive de-differentiation. In fact, the circadian clock has been extensively implicated in redox-biology.…”
Section: Role Of Circadian Clocks In Cancermentioning
confidence: 99%